Dampak Negatif Pernikahan Dini dan Upaya Pencegahannya Melalui Pendidikan Agama Islam - Febi Nina Barokah; Giyarsi Giyarsi (Journal on Education, 2024)
This research aims to explore the detrimental impacts of early marriage and the preventive measures through Islamic religious education in Purbosari Village. The employed research methodology encompasses a literature review, seeking information on the connection between early marriage and its impacts through similar research journals. Additionally, augmented reality and virtual reality are utilized in collaboration with the Purbosari village community to gather insights into the consequences of early marriage and preventive measures through religious education. The findings of this study highlight the crucial role of Islamic religious education in deterring early marriage. The Islamic values imparted through religious education, such as venerating knowledge, safeguarding reproductive health, and fostering harmonious families, can serve as a foundation for adolescents to postpone marriage until adulthood.